2006
DOI: 10.1007/s10549-006-9171-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjuvant breast cancer chemotherapy on cognitive function from the older patient’s perspective

Abstract: Approximately half of these older women perceived a decline in cognitive function from before to 6 months after chemotherapy. This perceived decline in cognitive function was most pronounced in patients with preexisting memory complaints. Further prospective study is needed to confirm these observations, correlate perceived memory changes with objective findings, and identify subgroups at special risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 13 publications
1
93
1
3
Order By: Relevance
“…Third, older people with cognitive impairment are more frequently isolated (34), and turn away persons who want to help, to avoid facing their difficulties (35). Finally, it is increasingly reported that chemotherapeutic agents can worsen the patient's cognitive status (36)(37)(38). Thus, it is obvious those patients with cognitive impairment at the start of chemotherapy are more vulnerable, and that their vulnerability can be worsened by chemotherapeutic agents (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Third, older people with cognitive impairment are more frequently isolated (34), and turn away persons who want to help, to avoid facing their difficulties (35). Finally, it is increasingly reported that chemotherapeutic agents can worsen the patient's cognitive status (36)(37)(38). Thus, it is obvious those patients with cognitive impairment at the start of chemotherapy are more vulnerable, and that their vulnerability can be worsened by chemotherapeutic agents (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Self‐reported cognitive function generally correlates with objective testing,6, 13 predicts impairment and dementia,14, 15, 16 and relates to abnormalities on neuroimaging even in the absence of objective deficits 17. Unfortunately, to the best of our knowledge, little is known regarding cognitive function outcomes and their time course in older survivors of breast cancer because past research has focused on younger patients, had few older survivors, did not include baseline function, and/or lacked long‐term follow‐up 18, 19, 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%
“…Ambos tipos de datos ofrecen información relevante. Un trabajo evaluó la percepción de 45 mujeres mayores con cáncer de mama (edad media 70 años) y apreciaron que la mitad de ellas consideraban que sus capacidades habían disminuido, sobre todo la capacidad de aprender información nueva (49%), seguida de memoria de trabajo (29%) y recuerdo remoto (20%) (20) ; otro estudio encuentra un elevado porcentaje de quejas cognitivas en memoria y concentración, aún presentes tras 18 meses del tratamiento, por lo que cuestionan la sensibilidad de las pruebas objetivas a sutiles déficit que pueden alterar la vida del paciente (21) .…”
Section: Estudios Longitudinalesunclassified